Association of serum immunoglobulin M and immunoglobulin G antibody levels with different indicators of metabolic syndrome - Manali Sinharay; Pritam Chowdhury; Anindya Dasgupta; Arindam Karmakar (Asian Journal of Medical Sciences, 2023)
Background: Metabolic syndrome (MS) is an assemblage of biochemical derangements of glucose metabolism, dyslipidemia, hypertension, and central obesity allied with implacable low-grade inflammation.